Identity and gender in gypsy culture - Sathler, Deborah (Revista do Colóquio, 2024)
This article addresses issues related to gypsy groups located in Rio de Janeiro. Using oral life history procedures, we sought to requalify the values ​​of Roma and Calon gypsy culture as filtered by two iconic characters: Mio Vacite and Ramona Torres. The examination of these interviews, in turn, is a path to understanding the performances of identity and gender and the alleged group memory, which allows us to see the strategies of internal and external coexistence, conditions that highlight factors that emerge from supposed tradition in confrontation with modernity. Artistic manifestations are highlighted as analytical means that, ultimately, reveal original and diverse positions present in complementary cultural spaces.